Toxicity, baseline of susceptibility, detoxifying mechanism and sublethal effects of chlorogenic acid, a potential botanical insecticide, on Bemisia tabaci - Wang, Ran; Zhang, Qinghe; Qu, Cheng; Wang, Qian; Wang, Jinda; Luo, Chen (Frontiers in Plant Science, 2023)
Bemisia tabaci is a threat to agriculture throughout the world because of its potential to cause devastating damage to crop plants. Chlorogenic acid is a bioactive pesticidal phytochemical agent that has significant lethal effects against insect pests. We here determined the baseline susceptibility of a laboratory strain of B. tabaci to chlorogenic acid and 11 other popular insecticides, and measured the susceptibility and cross-resistance of several field-collected populations of B. tabaci to chlorogenic acid and four common insecticides. Chlorogenic acid had the highest toxicity of all tested insecticides. The 12 field-collected B. tabaci populations were highly susceptible to chlorogenic acid, and there was no cross-resistance detected between chlorogenic acid and the other tested insecticides. Furthermore, analysis of cytochrome P450 monooxygenase (P450) gene expression and enzyme activity in B. tabaci after treatment with the median lethal concentration (LC50) of chlorogenic acid suggested that enhanced P450 activity could be involved in chlorogenic acid detoxification. We subsequently evaluated the sublethal effects of chlorogenic acid, and found that treatment with the 25% lethal concentration (LC25) prolonged the duration of two developmental stages, reduced fecundity, and decreased survival rates of treated B. tabaci compared to untreated insects. Overall, these findings demonstrate the strong toxicity and significant sublethal effects of chlorogenic acid on B. tabaci, and suggest that high P450 gene expression may be associated with chlorogenic acid detoxification.